Sovereign Defaults in Court - Julian Schumacher; Christoph Trebesch; Henrik Enderlein (Center for Economic Studies and ifo Institute (CESifo), 2018)
For centuries, defaulting governments were immune from legal action by foreign creditors. This paper shows that this is no longer the case. Building a dataset covering four decades, we find that creditor lawsuits have become an increasingly common feature of sovereign debt markets. The legal developments have strengthened the hands of creditors and raised the cost of default for debtors. We show that legal disputes in the US and the UK disrupt government access to international capital markets, as foreign courts can impose a financial embargo on sovereigns. The findings are consistent with theoretical models with creditor sanctions and suggest that sovereign debt is becoming more enforceable. We discuss how the threat of litigation affects debt management, government willingness to pay, and the resolution of debt crises.
Keywords: F34; G15; H63; K22; 330; sovereign default; enforcement; government financing; debt restructuring